Correlation in the discharges of neighboring rat retinal ganglion cells during prenatal life. - Maffei, L (1990)
The spontaneous discharges of neighboring retinal ganglion cells were recorded simultaneously in anesthetized prenatal rats between embryonic days 18 and 21. We report here that in the majority of cases the firings of neighboring retinal ganglion cells are strongly correlated during prenatal life. Correlation in the discharges of neighboring cells during development has long been suggested as a way to consolidate synaptic connections with a target cell onto which they converge, a model first proposed by Hebb. Correlation in the activities of neighboring neurons in the retina could be the basis of developmental processes such as refinement of retinotopic maps in the brain and segregation of the inputs from the two eyes.